Determination of some toxic elements such as arsenic, selenium, chromium and lead using icp-ms and gf-aas in rural ground water in Terengganu, Malaysia - Rahman, Md. Mokhlesur; Miskon, Mohd Fuad; Yunus, Kamaruzzaman; Wan Nik, Wan Mohd Norsani (2012)
ABSTRACT